Deterritorialising mental health: unfolding service user experience - Ian Tucker (2006)
Mental health has a long history of proving to be a tough concept to define. Multiple forms of knowledge and representation seek to inform as to the nature of mental health, all contributing to the production of immense complexity as to the experience of living with mental health difficulties. This thesis sets out to explore this, by getting as close as possible to mental health service users’ actual experiences. A range of forms of knowledge that pertain to inform as to service users’ experiences are explored, prior to analysing a corpus of interviews with service users. These are analysed through the development of a Deleuzian Discourse Analysis. Service users’ experiences are analysed in terms of the relation between discursive and non-discursive factors, which include forms of mainstream psychiatric discursive practice, such as the application of diagnostic criteria and administration of treatments, along with how such practices are experienced in non-discursive dimensions of service user embodiment and space. The challenges facing service users are seen to operate around identity and control in relation to forms of psychiatric knowledge, along with presenting particular problems with regard to how user embodiment is felt, primarily in relation to psychiatric medication, and how these are driven into the production of service user spaces, i.e. day centres. Finally, a politics of affectivity is offered, as a way to unfold the complexity of service user experience, and to emphasise the existence and potential for change that can be gained through deterritorialising mental health.